Tear-resistant biodegradable film bag modified material and preparation method thereof
By using materials such as polyadipic acid/butylene terephthalate, L-lactide-co-ε-caprolactone and other fillers, tear-resistant biodegradable membrane bag modification materials were prepared, which solved the problem of poor tear resistance performance of existing membrane bags under low blowing ratio conditions and reduced filling costs.
Patent Information
- Application Number
- CN202411438447.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-03-21
AI Technical Summary
The existing biodegradable membrane bags have poor tear resistance under low inflation ratio conditions and are high in filling costs, resulting in the high price of individual membrane bags.
The film bag modification material was prepared by melt extrusion and cooling pelletizing, and the film bag was blown under the condition of a blow ratio of less than 1:1.
The tear resistance strength of the film bag is significantly improved, and it is especially suitable for low blowing ratio conditions, while reducing the filling cost and reducing the amount of resin material addition.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of packaging materials, and in particular to a tear-resistant biodegradable film bag modified material and a preparation method thereof. Background Art
[0002] Biodegradable materials refer to plastics that can be completely degraded by microorganisms (such as bacteria, fungi and algae) into carbon dioxide and / or methane, water and mineralized inorganic salts of the elements they contain, as well as new biomass under appropriate and predictable natural environmental conditions. Biodegradable materials can replace ordinary petrochemical plastics, thereby effectively reducing the "white pollution" problem caused by traditional plastics to the environment. At present, the market often uses biodegradable materials filled with inorganic mineral powders to produce shopping bags, milk tea bags, roll bags, express bags, garbage bags, etc. Most of the fillers are calcium carbonate, talcum powder, kaolin, etc. Although their performance can meet the use requirements, because inorganic mineral powders are produced by grinding ores, their particle shape is irregular polyhedron, the particle size distribution is wide, and the compatibility with resin materials is poor, resulting in the production of biodegradable materials. The performance decays significantly with the increase of the filling amount, especially under the condition of low blowing ratio (such as less than 1:1) for blowing film bag making, the longitudinal tear resistance of the produced film bag decreases significantly. Therefore, for shopping bags of the same specifications and sizes, in order to maintain good tear resistance, the filling ratio can only be reduced, resulting in the high price of a single film bag; in addition, the stiffness of film products is improved by polylactic acid resin (PLA), but PLA is not only expensive, but also with the increase of PLA dosage, the orientation tear and elongation at break of the film will deteriorate. Based on this, the present application proposes a tear-resistant biodegradable film bag modified material and a preparation method thereof. Summary of the invention
[0003] The main purpose of the present application is to provide a tear-resistant biodegradable film bag modified material and a preparation method thereof, aiming to solve the technical problem of poor tear resistance of existing biodegradable film bags.
[0004] To achieve the above-mentioned purpose, the present application proposes a tear-resistant biodegradable film bag modified material, which comprises the following components by weight: 50-80 parts of polybutylene adipate / terephthalate, 1-10 parts of L-lactide-co-ε-caprolactone, 5-35 parts of anhydrous calcium sulfate, 0.3-1 part of lubricant, 0.2-1 part of dispersant, 0.3-1 part of compatibilizer and 0.2-1 part of antioxidant;
[0005] Wherein, the aspect ratio of the anhydrous calcium sulfate is 1 μm-10 μm.
[0006] Optionally, the preparation step of anhydrous calcium sulfate comprises:
[0007] Preparation of calcium sulfate dihydrate;
[0008] The calcium sulfate dihydrate is dissolved in water to form a suspension, and the suspension is continuously stirred in a closed reactor while being heated to 105° C.-115° C. to dehydrate and form calcium sulfate hemihydrate;
[0009] The calcium sulfate hemihydrate is then heated to 155° C.-165° C., and after removing half of the water, the anhydrous calcium sulfate is obtained.
[0010] Optionally, the L-lactide-co-ε-caprolactone is prepared by catalyzing, precipitating, filtering, washing and drying L-lactide and ε-caprolactone in a molar ratio of 80:20.
[0011] Optionally, the lubricant includes one or more of stearic acid, stearate, stearic acid amide, ethylene bis stearamide, oleic acid amide, erucic acid amide, glyceryl trihydroxystearate, polyethylene wax, oxidized polyethylene wax and pentaerythritol stearate.
[0012] Optionally, the dispersant includes one or more of sodium pyrophosphate, sodium polymetaphosphate, sodium orthophosphate, sodium silicate and potassium citrate.
[0013] Optionally, the compatibilizer includes one or more of a cyclic anhydride type compatibilizer, a carboxylic acid type compatibilizer, an epoxy type compatibilizer, an oxazoline type compatibilizer, an imide type compatibilizer, and an isocyanate type compatibilizer.
[0014] Optionally, the antioxidant is one or more of a hindered phenol antioxidant, a phosphite antioxidant, a thio antioxidant and a hindered amine antioxidant.
[0015] The present application also proposes a method for preparing a tear-resistant biodegradable film bag modified material, comprising the following steps:
[0016] The anhydrous calcium sulfate, lubricant, dispersant, compatibilizer and antioxidant are uniformly mixed to obtain powder;
[0017] Polybutylene adipate / terephthalate and L-lactide-co-ε-caprolactone are uniformly mixed to obtain a granular material;
[0018] The powder and the granular material are melt-extruded, cooled and pelletized to obtain a film bag modified material.
[0019] Optionally, the step of melt-extruding the powder and the granular material comprises:
[0020] The powder and the granular material are added into a twin-screw extruder and melt-extruded at 140° C.-165° C.
[0021] Optionally, after the step of melt-extruding, cooling and pelletizing the powder and the granular material to obtain the film bag modified material, the method further comprises:
[0022] The modified film bag material is added into the hopper of a co-extrusion film blowing machine, the temperature is set at 145° C.-165° C., film blowing is performed under the condition that the blowing ratio is less than 1:1, and then the finished packaging film bag is obtained through printing, winding and bag cutting.
[0023] The film bag modified material of the present application uses polybutylene adipate / terephthalate, L-lactide-co-ε-caprolactone, anhydrous calcium sulfate, lubricant, dispersant, compatibilizer and antioxidant as raw materials, and anhydrous calcium sulfate with an aspect ratio of 1μm-10μm as filler. It not only has the fineness of granular filler and the aspect ratio of short fiber filler, but also has good compatibility with resin, plastic, rubber, etc., and can be evenly dispersed. Compared with other inorganic mineral powder fillers, anhydrous calcium sulfate has a fibrous powder structure, which can form a dense The woven mesh structure can improve the tensile and tearing properties of the material. The present application selects anhydrous calcium sulfate with an aspect ratio of 1-10 microns. Since the common film thickness is 0.025mm-0.050mm, the 1-10 micron filling powder can be fully wrapped by the resin without being exposed, making the film surface smooth and free of granularity, which is very beneficial for the preparation of blown film products. The anhydrous calcium sulfate is a white loose needle-like substance, and the powder has a fiber columnar structure with certain support. As a film filler, it will improve the hardness and stiffness of the film, and as the filling The increase in filling amount will increase the feel and stiffness of the film, and further reduce the amount of resin material added, thereby reducing costs. At the same time, L-lactide-co-ε-caprolactone (PLCA) is used as a reinforcing resin to replace the traditional polylactic acid resin. PLCA is a copolymer that has the characteristics of high strength and fast degradation rate of left-handed polylactic acid (PLLA), and good toughness of polycaprolactone (PCL) material. It has good biocompatibility and biodegradable absorbability. Compared with PLA as a reinforcing resin, PLCA can show similar stiffness to PLA and good toughness. Its elongation and rigidity exist at the same time. Due to its good compatibility and coating properties, it can be stably combined with the filling material anhydrous calcium sulfate to form a stable homogeneous structure. After the action of a compatibilizer, a dispersant and a lubricant, a biodegradable film bag modified material is prepared. The film bag modified material has good tear resistance and is particularly suitable for film blowing and bag making under the condition of a blowing ratio of less than 1:1. It can significantly improve the tear difference problem of blowing small films and narrow bags, and at the same time reduce the filling cost. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0025] At present, biodegradable materials filled with inorganic mineral powders are often used in the market to produce film bag products. Most of the fillers are calcium carbonate, talcum powder, kaolin, etc., and PLA is relied on to improve stiffness. Although its performance can meet the use requirements, the tear resistance will decrease, especially when the film is blown to make bags under the condition of a blowing ratio of less than 1:1. The tearing problem of small blown films and narrow bags is prone to occur, and the filling cost is high, and the price of a single film bag remains high. Some methods are used in the prior art to improve the tear resistance of film bags. For example, patent CN202410179688.8 discloses a low-density mineral powder-filled biodegradable material and a preparation method. The biodegradable material is filled with calcium carbonate and needs to be added with 1-4 parts of low-density modified masterbatch, 10-20 parts of polyvinyl acetate, and 15-30 parts of paraffin to improve its high density problem. However, low-density modified masterbatch, polyvinyl acetate and paraffin materials are all non-biodegradable materials and will cause environmental pollution. Patent CN111748180b discloses a biodegradable film raw material combination and a biodegradable film material. The plant in its preparation method The fiber addition amount is 50-70 parts and the inorganic filler addition amount is 50-70 parts, but the addition amount of these two substances is relatively large, which may cause the inorganic filler to agglomerate and unevenly disperse, thereby reducing the strength of the plastic film. At the same time, the compatibility between plant fibers, inorganic fillers and other ingredients needs to be further improved; Patent CN202011325383.1 discloses a biodegradable composite material and a preparation method thereof. In the preparation method, 5-20 parts of plant fiber powder and 20-35 parts of talcum powder are used. The plant fiber is ground and dispersed by inorganic powder talcum powder. Although the compatibility of the components is improved, it may cause problems such as loose sealing and poor tearing.
[0026] In view of the technical problems existing in the above-mentioned prior art, the embodiments of the present application provide a tear-resistant biodegradable film bag modified material, which comprises the following components by weight: 50-80 parts of polybutylene adipate / terephthalate, 1-10 parts of L-lactide-co-ε-caprolactone, 5-35 parts of anhydrous calcium sulfate, 0.3-1 part of lubricant, 0.2-1 part of dispersant, 0.3-1 part of compatibilizer and 0.2-1 part of antioxidant;
[0027] Wherein, the aspect ratio of the anhydrous calcium sulfate is 1 μm-10 μm.
[0028] The film bag modified material of the present application adopts anhydrous calcium sulfate with an aspect ratio of 1μm-10μm as filler. It not only has the fineness of granular filler and the aspect ratio of short fiber filler, but also has good compatibility with resin, plastic, rubber, etc., and can be evenly dispersed. Compared with other inorganic mineral powder fillers, anhydrous calcium sulfate has a fibrous powder structure, which can form a dense woven mesh structure inside the resin, which can improve the tensile and tear properties of the material. The present application selects anhydrous calcium sulfate with an aspect ratio of 1-10 microns. Because the commonly used film thickness is 0.025mm-0.050mm, the 1-10 micron filling powder can be fully wrapped by the resin without being exposed, so that the film surface feels smooth and has no granular feel, which is very beneficial for the preparation of blown film products. In addition, anhydrous calcium sulfate is a white loose needle-like substance, and the powder shape is a fibrous columnar structure with certain support. As a film filler, it will improve the hardness and Stiffness: With the increase of filling amount, the feel and stiffness of the film will increase, and the amount of resin material added can be further reduced, thereby reducing costs. At the same time, PLCA is used as a reinforcing resin to replace traditional polylactic acid resin. PLCA is a copolymer that has the characteristics of high strength and fast degradation rate of PLLA and good toughness of PCL material. It has good biocompatibility and biodegradable absorbability. Compared with PLA as a reinforcing resin, PLCA can show similar stiffness to PLA and has good toughness. Its elongation and rigidity exist at the same time. Due to its good compatibility and coating properties, it can be stably combined with the filling material anhydrous calcium sulfate to form a stable homogeneous structure. After the action of compatibilizer, dispersant and lubricant, a biodegradable film bag modified material is prepared, which can not only improve the tear strength of the film under low blowing ratio conditions, but also solve the problem of filling cost reduction.
[0029] In the specific implementation process, polybutylene adipate / terephthalate is a genuine resin that meets the national standard, and its melt flow rate is 3g / 10min-5g / 10min (temperature 190°C, weight 2.16kg).
[0030] As an implementation method of the present application, the preparation step of anhydrous calcium sulfate includes:
[0031] Preparation of calcium sulfate dihydrate;
[0032] The calcium sulfate dihydrate is dissolved in water to form a suspension, and the suspension is continuously stirred in a closed reactor while being heated to 105° C.-115° C. to dehydrate and form calcium sulfate hemihydrate;
[0033] The calcium sulfate hemihydrate is then heated to 155° C.-165° C., and after removing half of the water, the anhydrous calcium sulfate is obtained.
[0034] Specifically, the steps of preparing calcium sulfate dihydrate include: reacting calcium carbonate with sulfuric acid to obtain calcium sulfate dihydrate; or reacting calcium chloride solution with soluble sulfate to obtain calcium sulfate dihydrate.
[0035] The anhydrous calcium sulfate of the present application is calcium sulfate powder that has been gradually dehydrated, has a white loose needle-like structure, a relative density of 2.96, a melting point of 1450°C, a heat resistance of 1000°C, high temperature resistance, acid and alkali resistance, chemical corrosion resistance, toughness, electrical insulation, and high strength. It is easy to carry out surface treatment, has a pH value close to neutral, has excellent reinforcing function and flame retardancy, and is used as a filler for biodegradable materials. It can not only improve the tensile and tearing properties of the material, but also increase the stiffness of the film, and can replace traditional inorganic mineral powders such as calcium carbonate, talcum powder, and kaolin.
[0036] As an implementation method of the present application, the L-lactide-co-ε-caprolactone is prepared by catalysis, precipitation, filtration, washing and drying of L-lactide and ε-caprolactone in a molar ratio of 80:20.
[0037] In the specific implementation process, L-lactide and ε-caprolactone are added to a round-bottom flask at a molar ratio of 80:20, and a stannous octoate catalyst is added, and the molar ratio of the monomer to the catalyst is 5000:1. After the reaction system is dried, nitrogen is replaced several times, and the system is sealed after vacuuming. The reaction is stopped after 48 hours in an oven at 140°C. The crude product is dissolved with chloroform, precipitated with anhydrous ethanol, filtered, and washed to obtain a white product, namely L-lactide-co-ε-caprolactone.
[0038] As an embodiment of the present application, the lubricant includes one or more of stearic acid, stearate, stearamide, ethylene bisstearamide, oleamide, erucamide, trihydroxystearate, polyethylene wax, oxidized polyethylene wax and pentaerythritol stearate.
[0039] Preferably, the lubricant is compounded with calcium stearate, erucic acid amide, oxidized polyethylene wax, and pentaerythritol ester in a mass ratio of 3:3:1:3. It can penetrate into the particles and particles of each layer of poly(butylene adipate / terephthalate) and L-lactide-co-ε-caprolactone, reduce the interaction force between molecular chain segments, and reduce the "plasticizing torque". Before the resin material is plasticized, the lubricant can form a complex bond with the polar nodes of the resin to weaken the friction between the resin chain segments. After the resin is plasticized, the polar groups of the lubricant can weaken the interaction forces between molecules and molecular chain segments in the melt, making the resin melt easy to flow and reducing the melt viscosity, thereby improving the processing performance of the film product.
[0040] As an implementation method of the present application, the dispersant includes one or more of sodium pyrophosphate, sodium polymetaphosphate, sodium orthophosphate, sodium silicate and potassium citrate.
[0041] Preferably, the dispersant can be a compound of sodium pyrophosphate and sodium polymetaphosphate in a mass ratio of 3:4. The dispersant can generate a large amount of electrostatic mutual repulsion on the surface of the anhydrous calcium sulfate filler, avoid agglomeration of the anhydrous calcium sulfate, facilitate the uniform distribution of the anhydrous calcium sulfate in the resin, and improve the compatibility of the components, so that the prepared film bag modified material has good mechanical properties and processing properties.
[0042] As an implementation method of the present application, the compatibilizer includes one or more of a cyclic anhydride type compatibilizer, a carboxylic acid type compatibilizer, an epoxy type compatibilizer, an oxazoline type compatibilizer, an imide type compatibilizer, and an isocyanate type compatibilizer.
[0043] Preferably, the compatibilizer is cyclic anhydride EVA-G-MAH, epoxy GMA, succinimide or oxazoline. The compatibilizer can promote the interaction between polybutylene adipate / terephthalate and L-lactide-co-ε-caprolactone molecules to form a continuous phase. With the addition of the compatibilizer, the powder raw material can be dispersed more evenly, thereby promoting various aspects of the performance of the biodegradable film bag modified material.
[0044] As an implementation method of the present application, the antioxidant is one or more of a hindered phenol antioxidant, a phosphite antioxidant, a thio antioxidant and a hindered amine antioxidant.
[0045] Preferably, the antioxidant is a compound of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010) and tris[2.4-di-tert-butylphenyl] phosphite (antioxidant 168), which can improve the antioxidant properties of the film product, enhance the weather resistance of the film bag, and play a role in long-term stability.
[0046] The embodiment of the present application also provides a method for preparing a tear-resistant biodegradable film bag modified material, comprising the following steps:
[0047] Add anhydrous calcium sulfate, lubricant, dispersant, compatibilizer and antioxidant into a high-speed mixer, set the speed to 800r / min, stir for 3-5 minutes at room temperature and then discharge to obtain powder;
[0048] Add polybutylene adipate / terephthalate and L-lactide-co-ε-caprolactone into a high-speed mixer, stir for 1-3 minutes at room temperature, and discharge after mixing evenly to obtain granular material;
[0049] The powder and the granular material are melt-extruded, cooled and pelletized to obtain a film bag modified material.
[0050] The preparation method of the present application first mixes anhydrous calcium sulfate, a lubricant, a dispersant, a compatibilizer and an antioxidant in a high-speed mixer, so that they are evenly mixed during high-speed stirring, and then polybutylene adipate / terephthalate and L-lactide-co-ε-caprolactone are mixed in a high-speed mixer, and polybutylene adipate / terephthalate is reinforced by using L-lactide-co-ε-caprolactone as a reinforcing resin, and the two are allowed to interact with each other to form a continuous phase, and then melt-extruded, cooled and pelletized to obtain a film bag modified material.
[0051] As an implementation method of the present application, the step of melt-extruding the powder and the granular material comprises:
[0052] The powder and the granular material are added into a twin-screw extruder and melt-extruded at 140° C.-165° C.
[0053] The present application uses a twin-screw extruder to extrude powder and granular materials, and limits the temperature of the extrusion process, which can make the materials have a better compression effect, and improve the plasticity and fluidity of the materials, ensuring that the materials still have good plasticizing properties after subsequent granulation.
[0054] As an implementation method of the present application, after the step of melt-extruding the powder and the granular material, cooling and pelletizing to obtain the film bag modified material, the method further includes:
[0055] The modified film bag material is added into the hopper of a co-extrusion film blowing machine, the temperature is set at 145° C.-165° C., film blowing is performed under the condition that the blowing ratio is less than 1:1, and then the finished packaging film bag is obtained through printing, winding and bag cutting.
[0056] The above technical solution of the present application is described in detail below in conjunction with specific embodiments.
[0057] Example 1
[0058] A tear-resistant biodegradable film bag modified material is prepared by the following steps:
[0059] L-lactide and ε-caprolactone are catalyzed, precipitated, filtered, washed and dried at a molar ratio of 80:20 to obtain L-lactide-co-ε-caprolactone;
[0060] Calcium carbonate is reacted with sulfuric acid to produce calcium sulfate dihydrate;
[0061] The calcium sulfate dihydrate is dissolved in water to form a suspension, and the suspension is continuously stirred in a closed reactor while being heated to 110° C. to dehydrate and form calcium sulfate hemihydrate;
[0062] The hemihydrate calcium sulfate is then heated to 160° C. to remove half of the water to obtain anhydrous calcium sulfate; wherein the aspect ratio of the anhydrous calcium sulfate is 5 μm;
[0063] 250 g of anhydrous calcium sulfate was added into a high-speed mixer, and the speed was set to 800 r / min. During the stirring process, lubricants (3 g of calcium stearate, 3 g of erucamide, 1 g of oxidized polyethylene wax and 3 g of pentaerythritol ester), dispersants (3 g of sodium pyrophosphate and 4 g of sodium polymetaphosphate), compatibilizers (5 g of cyclic anhydride EVA-G-MAH, 3 g of epoxy GMA and 2 g of succinimide) and antioxidants (1 g of antioxidant 1010 and 2 g of antioxidant 168) were added. The mixture was stirred at room temperature for 4 minutes and then discharged to obtain a modified filler, which was put into a powder weight loss scale for standby use.
[0064] Add 640g of polybutylene adipate / terephthalate (Tunhe TH801T) and 80g of L-lactide-co-ε-caprolactone into a high-speed mixer, stir for 2 minutes at room temperature, mix evenly, discharge the mixture, and put it into a pellet weight loss scale for standby use; wherein the melt flow rate of polybutylene adipate / terephthalate is 4g / 10min (temperature 190°C, weight 2.16kg);
[0065] The parameters of the powder weight loss scale and the pellet weight loss scale are set according to the ratio, and the above materials are added into the twin-screw extruder through the powder weight loss scale and the pellet weight loss scale, and melt-extruded at 152°C, and then cooled and pelletized to obtain the film bag modified material;
[0066] The modified film bag material is added into the hopper of a single-layer co-extrusion film blowing machine, the temperature is set to 155°C, and the film is blown at a blowing ratio of 1:0.88. The film is then printed and rolled according to the requirements of the film bag product. The rolled film is bagged, slit and packaged to obtain a finished packaging film bag.
[0067] Example 2
[0068] A tear-resistant biodegradable film bag modified material is prepared by the following steps:
[0069] L-lactide and ε-caprolactone are catalyzed, precipitated, filtered, washed and dried at a molar ratio of 80:20 to obtain L-lactide-co-ε-caprolactone;
[0070] Calcium sulfate dihydrate is prepared by reacting a calcium chloride solution with a soluble sulfate;
[0071] The calcium sulfate dihydrate is dissolved in water to form a suspension, and the suspension is continuously stirred in a closed reactor while being heated to 105° C. to dehydrate and form calcium sulfate hemihydrate;
[0072] The hemihydrate calcium sulfate is then heated to 155° C. to remove hemihydrate to obtain anhydrous calcium sulfate; wherein the aspect ratio of the anhydrous calcium sulfate is 1 μm;
[0073] 300 g of anhydrous calcium sulfate was added to a high-speed mixer, and the speed was set to 800 r / min. During the stirring process, lubricants (3 g of ethylene bisstearamide, 3 g of polyethylene wax, 1 g of oleamide and 3 g of stearic acid), dispersants (3 g of sodium silicate and 4 g of sodium polymetaphosphate), compatibilizers (5 g of cyclic anhydride EVA-G-MAH, 3 g of epoxy-type GMA and 2 g of succinimide) and antioxidants (1 g of antioxidant 1076, 2 g of antioxidant 2) were added. 3010) stirring at room temperature for 3 minutes and then discharging the material to obtain the modified filler, which was put into a powder weight loss scale for standby use;
[0074] Add 590g of polybutylene adipate / terephthalate (Tunhe TH801T) and 80g of L-lactide-co-ε-caprolactone into a high-speed mixer, stir at room temperature for 1 minute, mix evenly, discharge, and put into a pellet weight loss scale for standby use; wherein, the melt flow rate of polybutylene adipate / terephthalate is 3g / 10min (temperature 190°C, weight 2.16kg);
[0075] The parameters of the powder weight loss scale and the pellet weight loss scale are set according to the ratio, and the above materials are added into the twin-screw extruder through the powder weight loss scale and the pellet weight loss scale, and melt-extruded at 140°C, and then cooled and pelletized to obtain the film bag modified material;
[0076] The modified film bag material is added into the hopper of a multi-layer co-extrusion film blowing machine, the temperature is set to 145°C, and the film is blown at a blowing ratio of 1:0.88. The film is then printed and rolled according to the requirements of the film bag product. The rolled film is bagged, slit and packaged to obtain a finished packaging film bag.
[0077] Example 3
[0078] A tear-resistant biodegradable film bag modified material is prepared by the following steps:
[0079] L-lactide and ε-caprolactone are catalyzed, precipitated, filtered, washed and dried at a molar ratio of 80:20 to obtain L-lactide-co-ε-caprolactone;
[0080] Calcium carbonate is reacted with sulfuric acid to produce calcium sulfate dihydrate;
[0081] The calcium sulfate dihydrate is dissolved in water to form a suspension, and the suspension is continuously stirred in a closed reactor while being heated to 115° C. to dehydrate and form calcium sulfate hemihydrate;
[0082] The hemihydrate calcium sulfate is then heated to 165° C. to remove hemihydrate to obtain anhydrous calcium sulfate; wherein the aspect ratio of the anhydrous calcium sulfate is 10 μm;
[0083] 350 g of anhydrous calcium sulfate was added to a high-speed mixer, and the speed was set to 800 r / min. During the stirring process, a lubricant (3 g of glycerol, 3 g of erucamide, 1 g of oxidized polyethylene wax and 3 g of stearic acid), a dispersant (3 g of sodium orthophosphate and 4 g of potassium citrate), a compatibilizer (5 g of cyclic anhydride EVA-G-MAH, 3 g of epoxy-type GMA, and 2 g of oxazoline) and an antioxidant (1 g of antioxidant 1076 and 2 g of antioxidant 168) were added. The mixture was stirred at room temperature for 5 minutes and then discharged to obtain a modified filler, which was put into a powder weight loss scale for standby use.
[0084] Add 540g of polybutylene adipate / terephthalate (Tunhe TH801T) and 80g of L-lactide-co-ε-caprolactone into a high-speed mixer, stir for 3 minutes at room temperature, mix evenly, discharge the mixture, and put it into a pellet weight loss scale for standby use; wherein the melt flow rate of polybutylene adipate / terephthalate is 5g / 10min (temperature 190°C, weight 2.16kg);
[0085] The parameters of the powder weight loss scale and the pellet weight loss scale are set according to the ratio, and the above materials are added into the twin-screw extruder through the powder weight loss scale and the pellet weight loss scale, and melt-extruded at 165°C, and then cooled and pelletized to obtain the film bag modified material;
[0086] The modified film bag material is added into the hopper of a single-layer co-extrusion film blowing machine, the temperature is set to 165°C, and the film is blown at a blowing ratio of 1:0.88. The film is then printed and rolled according to the requirements of the film bag product. The rolled film is bagged, slit and packaged to obtain a finished packaging film bag.
[0087] Comparative Example 1
[0088] Compared with Example 1, anhydrous calcium sulfate was replaced by calcium carbonate with a particle size D97<0.0065 mm, and the other steps remained unchanged.
[0089] Comparative Example 2
[0090] Compared with Example 1, anhydrous calcium sulfate was replaced with talcum powder with a particle size D97<0.020 mm, and the other steps remained unchanged.
[0091] Comparative Example 3
[0092] Compared with Example 1, anhydrous calcium sulfate was replaced with 50 g of talcum powder with a particle size D97 < 0.020 mm and 250 g of calcium carbonate with a particle size D97 < 0.0065 mm, and the other steps remained unchanged.
[0093] Experimental example
[0094] The tensile strength, elongation at break and tear strength of the film bag products obtained according to the film bag modified materials in the examples and comparative examples were tested, and the test results are shown in Table 1 below.
[0095] Table 1
[0096]
[0097]
[0098] As can be seen from Table 1, the tensile strength, elongation at break and tear strength of the film bag products of Examples 1-3 of the present application are significantly improved compared with the film bag products of Comparative Examples 1-3, and the transverse and longitudinal tear strengths of the film bag products of Examples 1-3 are both >8.5MPa, indicating that the anhydrous calcium sulfate used as the filling system in the present application is superior to the filling system of inorganic mineral powder calcium carbonate, talcum powder or a mixture of the two, and can significantly improve the tear strength of the film bag products under low blowing ratio conditions.
[0099] The above description is only an optional embodiment of the present application, and does not limit the patent scope of the present application. All equivalent structural transformations made using the contents of the present application specification under the inventive concept of the present application, or direct / indirect application in other related technical fields are included in the patent protection scope of the present application.
Claims
1. A tear-resistant biodegradable film bag modified material, characterized in that: The invention comprises the following components by weight: 50-80 parts of polybutylene adipate / terephthalate, 1-10 parts of L-lactide-co-ε-caprolactone, 5-35 parts of anhydrous calcium sulfate, 0.3-1 part of lubricant, 0.2-1 part of dispersant, 0.3-1 part of compatibilizer and 0.2-1 part of antioxidant; Wherein, the aspect ratio of the anhydrous calcium sulfate is 1 μm-10 μm.
2. The tear-resistant biodegradable film bag modified material according to claim 1, characterized in that: The preparation steps of anhydrous calcium sulfate include: Preparation of calcium sulfate dihydrate; The calcium sulfate dihydrate is dissolved in water to form a suspension, and the suspension is continuously stirred in a closed reactor while being heated to 105° C.-115° C. to dehydrate and form calcium sulfate hemihydrate; The calcium sulfate hemihydrate is then heated to 155° C.-165° C., and after removing half of the water, the anhydrous calcium sulfate is obtained.
3. The tear-resistant biodegradable film bag modified material according to claim 1, characterized in that: The L-lactide-co-ε-caprolactone is prepared by catalyzing, precipitating, filtering, washing and drying L-lactide and ε-caprolactone in a substance ratio of 80:
20.
4. The tear-resistant biodegradable film bag modified material according to claim 1, characterized in that: The lubricant includes one or more of stearic acid, stearate, stearic acid amide, ethylene bis stearamide, oleic acid amide, erucic acid amide, glyceryl trihydroxystearate, polyethylene wax, oxidized polyethylene wax and pentaerythritol stearate.
5. The tear-resistant biodegradable film bag modified material according to claim 1, characterized in that: The dispersant includes one or more of sodium pyrophosphate, sodium polymetaphosphate, sodium orthophosphate, sodium silicate and potassium citrate.
6. The tear-resistant biodegradable film bag modified material according to claim 1, characterized in that: The compatibilizer includes one or more of a cyclic anhydride type compatibilizer, a carboxylic acid type compatibilizer, an epoxy type compatibilizer, an oxazoline type compatibilizer, an imide type compatibilizer, and an isocyanate type compatibilizer.
7. The tear-resistant biodegradable film bag modified material according to claim 1, characterized in that: The antioxidant is one or more of a hindered phenol antioxidant, a phosphite antioxidant, a thio antioxidant and a hindered amine antioxidant.
8. A method for preparing the tear-resistant biodegradable film bag modified material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The anhydrous calcium sulfate, lubricant, dispersant, compatibilizer and antioxidant are uniformly mixed to obtain powder; Polybutylene adipate / terephthalate and L-lactide-co-ε-caprolactone are uniformly mixed to obtain a granular material; The powder and the granular material are melt-extruded, cooled and pelletized to obtain a film bag modified material.
9. The method for preparing the tear-resistant biodegradable film bag modified material according to claim 8, characterized in that: The step of melt-extruding the powder and the granular material comprises: The powder and the granular material are added into a twin-screw extruder and melt-extruded at 140° C.-165° C.
10. The method for preparing the tear-resistant biodegradable film bag modified material according to claim 8, characterized in that: After the step of melt-extruding the powder and the granular material, cooling and pelletizing to obtain the film bag modified material, the method further comprises: The modified film bag material is added into the hopper of a co-extrusion film blowing machine, the temperature is set at 145° C.-165° C., film blowing is performed under the condition that the blowing ratio is less than 1:1, and then the finished packaging film bag is obtained through printing, winding and bag cutting.
Citation Information
Patent Citations
A biodegradable film raw material combination and biodegradable film material
CN111748180B
Biodegradable composite material and preparation method thereof
CN112521730A
Low-density mineral powder filled biodegradable material and preparation method thereof
CN117986818A
Method for improving processing flowing property of polymer
CN112812520A
Preparation method of degradable plastic mixed particles
CN114133705A